Effect of Exposure to Boarding Schooling on Pregnancy among School-Going Teenagers: A Retrospective Case-Control Study in Eastern Province, Zambia - Nasson N. Tembo; Choolwe Jacobs; Catherine N. Maliko; Patrick Musonda (MDPI AG, 2023)
Cases of teenage pregnancy remain high in Eastern Province of Zambia-contributing to health, economic, and social problems. This study sought to determine the effect of exposure to boarding schooling on pregnancy among school-going teenagers, taking into account individual and school characteristics. This was a retrospective case-control study involving 261 cases and 522 controls obtained from nine boarding and nine day secondary schools, between 2019 and 2021. STATA 16.1 MP was used for all statistical analyses at a 5% level of significance. Unadjusted and adjusted effects were obtained using logistic regression analysis-taking into account 18 school clusters. Cases had a mean age of 17.4 years (±1.14 years), controls were 16.1 years (±1.71 years) old on average, and 315 (40%) of the participants were exposed to boarding schooling. The unadjusted odds of pregnancy in the exposed and unexposed (day scholars) girls were 0.25 and 0.73, respectively (cOR = 0.34, CI: 0.24-0.48, p < 0.0001). Adjusting for other characteristics, teenage girls in boarding schools had 60% lower odds of pregnancy (aOR = 0.40, CI = 0.16-1.00, p = 0.049). In light of this evidence, enrollment of teenage girls in boarding schools is encouraged to help mitigate teen pregnancy in the province. Additionally, a multicenter prospective study is recommended.